With young people in mind - Berglund, Lina (2007)
This master's thesis is about the process of developing young people's educational environments. By keeping a weekly diary, I have followed three months of a UK secondary school ground development. The diary has been written with focus on young people and the design development. By having the diary as a tool, I aimed to develop an understanding of the design process and to be able to reflect upon important, child-related issues that were being addressed during the course of the design development. With this method I wanted to target the main difficulties in the process of designing a school ground with the best interest of young people. Through the diary writing I found two subjects which I believe are central in English school ground developments. The first issue is about making the pupils' voices acknowledged in the design process. The second is how the external design evolves around an idea of security and how the design is compromised by a feeling of fear. I have penetrated these issues in two independent articles. I use theorists such Maria Kylin, Mats Lieberg, Sofia Cele, Zygmunt Bauman and Peter Blatchford amongst other ones. One of the main conclusions derived from the process of writing the article about pupil engagement, is to first of all question myself as a landscape architect -to whose interest am I designing ?-. Is it important to have my design appreciated by my peers or by the pupils? In order to answer that question appropriately, one has to acknowledge the differences there are in spatial and environmental appreciation and perception between young people (which equals the pupils) and adults (which equals the people involved in the design team). It is also essential to acknowledge that pupil participation as a vital part of a school ground design development. The pupils have right to be part of the planning of their everyday environment, which also is stated in UN's Convention of the Rights of the Child from 1989. It is necessary to develop a sustainable strategy where the pupils can be engaged in the design of the school grounds, but also is a strategy that works within a typical tight design programme. From the process of writing the second article about how ideas of security informs the school ground design, I came to realise the complexity of fear, both in a historic perspective and in our contemporary period. The subject is tied in to the previous article and the differences in perception of and usage of space. The young people wish to find free zones in the public realm and the adults respond to this need by applying restrictions and other measures of control. These restrictions, such as security fencing a school ground have not only an impact on the pupils' experiences in the school environment, but also an impact on the members in the community. The real users' needs ought to be understood and addressed in a school ground design process in order to plan a sustainable development.